The Language of the Old Czech Legenda "O Svaté Kateřině" - Cummins, George M. (Slavistische Beitraege, 1975)
The following three essays and transcription of the Old Chech "Legenda o svaté Kateřině" do not make up a rigogous textual study in the familiar sense - this work was completed half a century and more ago by the philologists Spina and Gebauer. Chapter I seeks to identify multiple sets of spellings habits from close study of the single copy ot this fourteenth century poetic masterpiece. Chapter II studies the literary stylization of tense and aspect...